The complete guide to portfolio construction and management - Snopek, Lukasz (Chichester, U.K. ; Hoboken, N.J. : Wiley, 2012)
'The Complete Guide to Portfolio Construction and Management is a one-stop guide to portfolio construction and management in a modern context'--
pt. 1. Investors and risk -- pt. 2. Asset classes and their degree of risk -- pt. 3. The market -- pt. 4. Valuation of financial assest -- pt. 5. Three practical approaches to security selection : Buffett, Graham and Lynch -- pt. 6. Behavioural finance -- pt. 7. Forecasting market movements -- pt. 8. Modelling market movements -- pt. 9. Portfolio construction and management -- pt. 10. Attractiveness of the different asset classes.
Includes bibliographical references and index.
Keywords: Portfolio management; Electronic books